Teaching for the Tithe: donor expectations and the Matrona's Tithe - Dalton, Krista N. (AJS review, 2020)
This article examines a story in the Jerusalem Talmud depicting a wealthy woman who expects Torah instruction in exchange for her tithes. This textual example is used as a lens through which to view the changing social, religious, and economic relationships of Roman Syria Palaestina, whereby the biblically described institution of tithing to priests expanded to include priestly descendent rabbis. Giving the priestly tithe to a rabbi, while advantageous in a period of rabbinic fundraising, presented a distinct set of challenges as it came to resemble patronage practices associated with Roman elites. Through close textual analysis of the wealthy woman's tithe, the prominence and consequences of scholastic donations are examined, both in rabbinic literature and in the broader late ancient Mediterranean.